Heavy Atom Effect on the Room Temperature Chemiluminescent Phosphorescence of the Tricyclic 1,2-Dioxetanes - Sun, Chung-Wen; Chen, Shun-Chi; Fang, Tai-Shan (Asian Journal of Chemistry, 2013)
1,2-Dioxetane tricyclic compound (1a) and 5-halo substituted of 1,2-dioxetane tricyclic compounds (2a, 3a) were synthesized from 1,4-dioxin acenaphthylene compound (1) and 5-halo substituted 1,4-dioxin acenaphthylene compounds (2, 3), by reacting with singlet-oxygen (1O2) at 238 K and their chemiluminescent efficiency both in fluorescence and phosphorescence was studied while upon heating to temperatures between 313-353 K in dichloromethane. The chemiluminescent phosphorescence can be detected along with the chemiluminescent fluorescence when compounds (2a, 3a) are decomposed thermally to the corresponding naphthalene diesters (2b, 3b). Experimental evidences for formation of the dioxetanes 1a-3a are the observed chemiluminescence spectra which are consistent with the photoluminescence spectra of the excited compounds 1b-3b. Temperature-dependent kinetic measurements reveal an increase of room temperature chemiluminescent phosphorescence efficiency from triplet chemiexcitation processes due to the internal heavy atom effect of compound 3a.